(untitled) (Majalah Kedokteran Bandung, 2017)
Sindrom malnutrisi-inflamasi merupakan masalah pada pasien dalam hemodialisis. Peningkatan inflamasi menyebabkan risiko malnutrisi meningkat. Massa lemak menggambarkan perubahan status nutrisi yang lebih baik pada pasien hemodialisis (HD). Peningkatan TNF-Î± menyebabkan produksi ROS lebih tinggi dan akan ditangkap oleh vitamin E. Vitamin E dan TNF-Î± keduanya disimpan di massa lemak dan bersikulasi dalam darah. Penelitian ini bertujuan mengetahui perbedaan kadar vitamin E dan TNF-Î± pada dua kelompok massa lemak berbeda pasien dalam HD kronik. Penelitian ini merupakan penelitian observasional analitik dengan metode potong lintang pada 42 pasien pria yang menjalani HD kronik di RS Dr. Hasan Sadikin Bandung periode September–Oktober 2016. Massa lemak diperiksa dengan alat BIA (bioelectric impedance analyzer) dan dibagi ke dalam dua kelompok, yaitu lebih dan normal/kurang. Vitamin E dan TNF-Î± diperiksa dengan kromatografi dan ELISA. Analisis statistik menggunakan uji beda dua kelompok tidak berpasangan. Hasil penelitian menunjukkan kadar vitamin E lebih tinggi pada massa lemak lebih daripada normal/kurang (p=0,042). Kadar TNF-Î± lebih rendah pada massa lemak lebih daripada normal/kurang namun tidak bermakna (p=0,443). Subjek usia>55 tahun, kadar vitamin E lebih tinggi pada massa lemak lebih daripada normal/kurang (p=0,029). Massa lemak lebih dengan lama HD >24 bulan, kadar vitamin E lebih rendah daripada HD â‰¤24 bulan (p=0,005). Massa lemak normal/kurang dengan lama HD >24 bulan, kadar TNF-Î± lebih tinggi daripada HD â‰¤24 bulan (p=0,031). Penelitian ini menyimpulkan, kadar vitamin E lebih tinggi pada kelompok subjek dengan massa lemak lebih daripada normal/kurang. Kadar vitamin E pada massa lemak lebih dengan lama HD >24 bulan, lebih rendah daripada â‰¤24 bulan. Tidak terdapat perbedaan kadar TNF-Î± pada kedua kelompok massa lemak, namun kadar TNF-Î± lebih tinggi pada massa lemak normal/kurang dengan lama HD >24 bulan daripada â‰¤24 bulan. [MKB. 2017;49(3):192–8] Kata kunci: HD kronik, massa lemak, sindrom malnutrisi-inflamasi, TNF-Î±, vitamin E Difference between Vitamin E and Tumor Necrosis Factor Alpha (TNF-Î±) Levels based on Fat Mass Status in Chronic Hemodialysis Patients Malnutrition-inflammation syndrome is a problem frequently found in patients who undergo chronic hemodialysis (HD). Increased level of inflammation has a higher risk for malnutrition. Fat mass shows better nutritional status changes in HD patients. TNF-Î± will cause increased ROS production and will be scavenged by vitamin E that are both saved in fat mass. This study aimed to determine the difference between vitamin E and TNF-Î± levels in two fat mass groups of chronic HD patients. This study was a cross-sectional observational-analytic study on 42 male chronic HD patients at Dr. Hasan Sadikin General Hospital Bandung in the period of September–October 2016. Fat mass was measured by BIA and divided in two fat mass groups, higher and normal/lower mass groups. Vit E and TNF-Î± levels were measured by chromatography and ELISA. Non-paired groups difference test was used as the statistical analysis. The results showed a higher level of vitamin E in higher fat mass group than normal/lower group (p=0.042). TNF-Î± level tended to be lower in higher fat mass group than in the normal/lower group; however, the difference was not significant statistically (p=0.443). Subjects who were >55 years showed a higher level of vitamin E in hifher fat mass group than in normal/lower (p=0.029). The higher fat mass group with HD duration >24 months showed lower vitamin E level than those with the HD duration â‰¤24 months (p=0.005). Normal/lower fat mass group with a HD duration of >24 months showed a higher TNF-Î± level thanâ‰¤24 months(p=0.031). In conclusion, in chronic HD patients the vitamin E level is higher in the higher fat mass group than in the normal/lower group. The vitamin E level in the higher fat mass with HD duration of >24 months is lower than in the HD duration of â‰¤24 months. There is no significant difference in TNF-Î± level in the two fat mass groups; however, the TNF-Î± level is higher in normal/lower fat mass group with a duration of HD of >24 months than those with a duration of â‰¤24 months. [MKB. 2017;49(3):192–8] Key words: Chronic HD, fat mass, malnutrition inflammation syndrome, TNF-Î±, vitamin E